Low birth weight new born: epidemiological, therapeutic and evolutive aspects in the commune of Kara (TOGO) from 2014 to 2015 - Dr. Azoumah KD; Dr. Segbedji KAR; Dr. Douti KN; Dr. Ahouankpo KA; Dr. Tchagbele OB; Dr. Geraldo A; Dr. Douaguibe B; Dr. Balaka B; Dr. Agbere AD (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Low birth weight (LBW) is the third leading cause of neonatal death after neonatal infections and asphyxia. Objective: Describe the epidemiological, therapeutic and evolutionary effects of LBW neonates. Methods: This was an analytical retrospective study from January 1, 2014 to December 31, 2015, in three neonatal units in Kara commune concerning the LBW newborn. The main parameters studied were clinical, therapeutic and evolutionary. Results: Of 1712 newborns hospitalized, 527 were LBW (30.8%) of which 451 were included with 222 males (sex ratio 0.97). The average birth weight was 1775.72 g. Delivery was carried out through caesarean section in 16.9% mainly did about eclampsia (29.5%) and prævia hemorrhagic placenta (12.6%). The main co-morbidities were neonatal infections (55.4%) and perinatal asphyxia (12.9%). The treatment consisted of an antibiotic therapy (73.8%), an exclusive breastfeeding (43.7%) and Kangaroo Maternal Care (30.2%). Immediate results were marked by deaths in 18.8% after an average of 6 days hospital admission. The main factors significantly related to neonatal mortality were the early neonatal period, low sucking, hypotonia, high preterm birth, very LBW, inadequate pregnancy monitoring, referrals, perinatal asphyxia, artificial breastfeeding. Conclusion: The incidence of LBW remains high with significant mortality due to preventable factors, requiring actions to be coordinated from conception through the end of the period to improve the survival of these newborns.